Experience of diagnosis of congenital arterial anomaly in a child with bronchial obstruction: clinical case and summary - L.V. Besh; O.I. Matsyura; V.B. Yaskiv; M.V. Konyk; V.F. Petrov; LV. Dvorchyn; O.V. Omelyanenko; O.V. Malko; O.V. Pasternak (Zaslavsky O.Yu., 2017)
Congenital anomalies of the aortic arch are a large group of cardiovascular anomalies. Some of them are isolated; others are associated with congenital heart defects or genetic syndromes. There can be different clinical manifestations of these anomalies - from silent forms (accidentally discovered in the examination) to a critical circulatory disturbance, requiring surgical intervention in the first hours after the birth of the baby. The article describes clinical search of double aortic arch in a child and successful surgical treatment of this anomaly. This congenital defect of the aorta usually causes the greatest compression of airways compared to other vascular abnormalities. Double aortic arch develops due to absence of involution of distal IV right aortic arch. As a result, two IV arches keep on developing and join together in the left-sided descending thoracic aorta, thus surrounding the trachea and esophagus. Smaller of the two arches is often subjected to atresia, but it is still connected to the descending aorta, creating a complete vascular ring. As a double aortic arch pressures on the trachea and esophagus, it can cause airway obstruction and dysphagia in a patient. Therapeutic tactic depends on the intensity of symptoms, presence of concomitant anomalies or diseases, and many additional factors, which are analyzed and considered within the council of physicians of different specialties.